2021
DOI: 10.1186/s13023-021-01688-6
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in paediatric patients with movement disorders

Abstract: Background Movement disorders are a group of heterogeneous neurological diseases including hyperkinetic disorders with unwanted excess movements and hypokinetic disorders with reduction in the degree of movements. The objective of our study is to investigate the genetic etiology of a cohort of paediatric patients with movement disorders by whole exome sequencing and to review the potential treatment implications after a genetic diagnosis. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In light of the prelingual deafness and early‐adulthood‐onset dystonia in this case, combined with the family history and negative results of laboratory and imaging tests, the diagnosis of DDS was suspected. To make a differential diagnosis and predict DBS outcome as recommended, 3 WES was conducted, and the ACTB p.Arg183Trp variant was revealed. The ACTB gene encodes cytoplasmic β‐actin, which participates in many basic cellular processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of the prelingual deafness and early‐adulthood‐onset dystonia in this case, combined with the family history and negative results of laboratory and imaging tests, the diagnosis of DDS was suspected. To make a differential diagnosis and predict DBS outcome as recommended, 3 WES was conducted, and the ACTB p.Arg183Trp variant was revealed. The ACTB gene encodes cytoplasmic β‐actin, which participates in many basic cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…DBS has been widely used for treating dystonia, and therapeutic targets of the global pallidus internus (GPi) and the STN seem to have similar efficacy 6 . Kwong et al 3 concluded that GPi‐DBS responses varied among different monogenic forms of dystonia, and it did benefit a majority of patients. Among the 9 patients with DDS, the 4 who received GPi‐DBS were observed with lasting improvement 7–10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic causes were also identified from single cases involving heterozygous single allelic substitutions in TOR1A (c.907_909del, p.303_303del), 32,33 TUBB4A (c.38C>A, p.P13Q), THAP1 (c.122G>A, p.R41H), ATP1A3 (c.1825 G>A, p.D609N), ANO3 (c.2053A>G, p.S685G), 34 GNAL (c.2272G>A, p.G758R), KMT2B (c.3043C>T, p.R1015X), SLC6A3 (c.1634C>A, p.P545H), ADCY5 (c.139G>T, p.G47W), C19orf12 (c.273_274insA, p.P92Tfs*9), and SPG11 (c.4462_4463del, p.V1488fs) (Supplemental Table S3). 35 One patient had compound heterozygous variants in exon 1 (c.332 T>A, p.L111Q) and exon 5 (concomitant c.1499A>T, p.N500I) of PANK2, 36 and another patient had the compound heterozygous substitutions c.1072C>T (p.Gln358X) in exon 6 and c.496-497 (p.503-514) deletion in exon 1 of CYP27A1. 37 The clinical characteristics of patients harboring these variants are summarized in Table 3 ½T3 ½T3…”
Section: Clinical and Genetic Analysis In Single Cases Of Pathogenic ...mentioning
confidence: 99%
“…There are, to date, 10 reported cases in the literature, the first one described in a 2006 study in twins, 4 and the last one in 2021. 6 All of them displayed infant-onset deafness and dystonia starting in adolescence or young adulthood. In contrast with most of the reported cases, our patient has neither developmental delay nor cognitive impairment.…”
mentioning
confidence: 99%